Review on counter measures to coronavirus disease 2019 (COVID-19) pandemic, May 2020 - Taishi Kidaka; Sithumini M. W. Lokupathirage; Bungiriye Devinda Shameera Muthusinghe; Boniface Lombe Pongombo; Christida Estu Wastika; Zhouxing Wei; Shizuka Yoshioka; Mayumi Ishizuka; Yoshihiro Sakoda; Hiroaki Kariwa; Norikazu Isoda (The Japanese Journal of Veterinary Research, 2020)
[Abstract] An outbreak of novel coronavirus infection occurred in China at the end of 2019, which was designated as coronavirus disease 2019 (COVID-19), and spread to regions across Asia and ultimately all over the world. As of 21 May 2020, a total of more than 5 million cases with more than 350 thousand deaths were reported worldwide. Evaluation of the pathogenicity of the disease and determining the efficacy of control measures are essential for rapid containment of the disease. However, the world is facing difficulties in controlling COVID-19 at both of the national and global levels due to variations in pathogenicity of infection by severe acute respiratory syndrome coronavirus 2, the causal agent of COVID-19, and to diverse measures applied in each country based on their control capacities and policies. In the present review, we summarize the basic information and findings related to the COVID-19 pandemic, including pathogen agent, epidemiology, disease transmission, and clinical manifestations. Diagnosis, treatment, and preventive measures applied or under development all over the world are also reviewed to provide the opportunity to establish a more effective scenario for disease containment. Humanity has progressed by developing countless great technologies and immense scientific theories, however it may be a fact that we cannot conquer all risks to humanity. New findings and challenges for the unprecedented pandemic at the global level, such as COVID-19, should also contribute to preparedness for unknown diseases in future, similar to the lessons learnt from severe acute respiratory syndrome and the pandemic A (H1N1) pdm09 influenza.